Pertanggungjawaban Pelaku Tindak Kekerasan Pada Hewan: Kajian Hukum Perspektif Hukum Pidana - Verlina; Yudi Kornelis (Jurnal Supremasi, 2023)
The violence against animals in Indonesia is a problem in society that is prone to occur. As creatures of God, animals also have the right to live and their welfare is guaranteed. Many crimes that harm animals are committed by individuals who prioritize their own benefits and do not think about the feelings of the animals who are victims. As a rule of law, the law has a role in protecting all parties, including animals. The purpose of this research is to explore what kind of protection is given by the state to animals and to enforce sanctions against perpetrators of violence against animals. This study uses normative research methods with statutory approach methods. As a result, research shows that the problem of violence experienced by animals in Indonesia needs serious attention. Furthermore, the laws governing the protection of animals need to be updated because they are not in accordance with the current situation in terms of the protection that is regulated and the criminal sanctions that ensnare individuals are too light and it is necessary to evaluate their implementation in public life.